Capnocytophaga canimorsus tricuspid valve endocarditis. (2021) - Lindén, Sienna; Gilje, Patrik; Tham, Johan; Lindstedt, Sandra; Rasmussen, Magnus
Abstract: Capnocytophaga canimorsus is an uncommon cause of infective endocarditis (IE) and mainly affects persons with compromised immune-systems who have been in contact with dogs. We describe a case of C. canimorsus tricuspid valve IE in a 70 year-old dog-owner where diagnosis and treatment were delayed. The reason for the delayed diagnosis in this case was likely due to that initial blood cultures were negative due to preceding antibiotic treatment, discrepancies between echocardiographic investigations, and a thymoma and colonic polyps which were thought to explain the symptoms. A multi-diciplinary approach in cases with suspected IE might help to avoid diagnostic delays.